Asphalt shingle modeling and parameter estimation under short period loading condition. (18th January 2023) - Cui, Qihong; Hurtubise, Cory; Smith, Steven; Yang, James
Highlights: A series of tensile tests show that asphalt shingles should not simply be treated as an isotropic material. The representative volume element model for asphalt shingle is developed and validated through experimental results. Modeling asphalt shingles as orthotropic material is acceptable. Compared to other moduli, E 11 of asphalt shingle is most sensitive to the change of fiberglass volume ratio and the fiberglass filament elastic modulus. The change of asphalt-filler mixture elastic modulus will have an obvious influence on all the moduli of asphalt shingle. Abstract: Asphalt shingles are one of the major sources of insurance damage claims after a hailstorm. The mechanical behavior of asphalt shingles needs to be thoroughly investigated to evaluate their hail resistance performance. In this study, tensile tests are conducted on the asphalt shingles samples and one of the important components of asphalt shingles - the fiberglass base mat. The elastic moduli of samples cut from different orientations vary. The simplified representative volume element (RVE) model of asphalt shingle is developed, and its constituent material properties are estimated through optimization to ensure the simulation results match the experimental results. To investigate the effectiveness of modeling asphalt shingles as an orthotropic material, the developed asphalt shingle RVE model is used to estimate the effective orthotropic material model properties and the in-plane tensile tests simulation results can reasonably match the experimental results. Meanwhile, the effect of fiber volume ratio and constituent material properties on the asphalt shingle moduli are further investigated based on the asphalt shingle RVE model.